Inter-industry wage differentials and the gender wage gap: evidence from European countries - Gannon, Brenda; Plasman, Robert; Rycx, François; Tojerow, Ilan (Bonn, 2005)
"This study analyses the interaction between inter-industry wage differentials and the gender wage gap in six European countries using a unique harmonised matched employer-employee data set, the 1995 European Structure of Earnings Survey. Findings show the existence of significant inter-industry wage differentials in all countries for both sexes. While their structure is quite similar for men and women and across countries, their dispersion is significantly larger in countries with decentralised bargaining. These differentials are significantly and positively correlated with industry profitability. The magnitude of this correlation, however, is lower in countries with centralised and coordinated collective bargaining. Further results show that in all countries more than 80% of the gender wage gaps within industries are statistically significant. Yet, industries having the highest and the lowest gender wage gaps vary substantially across European countries. Finally, results indicate that industry effects explain between 0 and 29% of the overall gender wage gap."